Analisis Biaya Produksi Pabrik Tahu Pak Gareng di Purwogondo, Kartasura - Fadhilah Nurjanah; Novanda Saum Salsabila; Noor Laila Fitriana (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
Pak Gareng Tofu Factory is one of the small and medium enterprises engaged in tofu production in Purwogondo, Kartasura. The tofu factory established by Mr. Gareng was established in 2019 which is almost five years ago. This study aims to analyze production costs, load costs, work costs and factory overhead costs at Pak Gareng's Tofu Factory. This study uses a descriptive method with a quantitative approach. The results of the research from the total costs incurred during one month amounted to Rp. 90,230,000.00. In Pak Gareng's tofu factory there are 3 employees, of which 2 workers are in charge of making tofu and 1 is in charge of cutting tofu. The process of making tofu in this factory includes, washing soybeans, grinding soybeans, boiling soybeans, filtering soybeans, molding them into tofu, cutting tofu, and finally the tofu is ready to take. The workers at Pak Gareng's tofu factory usually work for 26 days a month.